Child Labor in China - Can Tang; Liqiu Zhao; Zhong Zhao (Institute for the Study of Labor (IZA), 2016)
We present the first systematic study on child labor in China. Child labor is not a negligible social phenomenon in China; about 7.74% of children aged from 10 to 15 were working in 2010, and they worked for 6.75 hours per day on average, and spent 6.42 hours less per day on study than other children. About 90% of child laborers were still in school and combined economic activity with schooling. Our results show that child labor participation is positively associated with school dropout rate. A child living in a rural area is more likely to work. Compared with place of residence, the gender of a child are less important. The educational level of the household head and its interaction with the gender of the household head seem to be unimportant. However, household assets per capita and household involvement in non-agricultural activities are negatively related to the incidence of child labor. A child from a household with more adults is less likely to work. The prevalence of child labor in China exhibits significant regional variations. The child labor incidence is correlated with the development level of each region: the Western region has the highest percentage of child labor, followed by the Eastern and Central region.
Keywords: J43; J81; O15; 330; China; child labor; school dropout; working hours